Improving Grade 4 Student Speaking Skills in Indonesian Language Lessons through Problem Based Learning Model - Nanik Yuni Setyowati (Universitas Sebelas Maret, 2020)
The purpose of this research is to improve the speaking skills of grade 4 students in Indonesian language lessons through the Problem Based Learning Model. This research is a classroom action research (PTK) which is carried out in three cycles, each cycle consisting of planning, implementation, observation, and reflection stages. The subjects of this study were the fourth grade students of SD Al Irsyad Al Islamiyyah 01 Purwokerto in the academic year 2020/2021, totaling 22 students. Data collection techniques using observation and tests. Data analysis includes data presentation, and drawing conclusions. Research shows that the application of the Problem Based Learning Model method can improve students' speaking skills in the material of extracting information from a character through interviews using a list of questions in class IV SD Al Irsyad Al Islamiyyah 01 Purwokerto academic year 2020/2021 as evidenced by the percentage of completeness of speaking skills in the cycle I was 68.5%, cycle 2 was 91% and cycle 3 increased to 95%.